2009
DOI: 10.1200/jco.2008.18.3301
|View full text |Cite|
|
Sign up to set email alerts
|

Phase II Trial of the Combination of Bevacizumab and Erlotinib in Patients Who Have Advanced Hepatocellular Carcinoma

Abstract: The combination of B + E in patients who had advanced HCC showed significant, clinically meaningful antitumor activity. B + E warrant additional evaluation in randomized controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
240
1
11

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(252 citation statements)
references
References 44 publications
0
240
1
11
Order By: Relevance
“…A second approach is to combine MTT targeting different molecular pathways. Preliminary results of a phase II trial combining bevacizumab with erlotinib showed a response rate of 20% and a median overall survival of 15.5 months [390]. However, these preliminary results must be validated by larger randomized trials.…”
Section: Future Directionsmentioning
confidence: 99%
“…A second approach is to combine MTT targeting different molecular pathways. Preliminary results of a phase II trial combining bevacizumab with erlotinib showed a response rate of 20% and a median overall survival of 15.5 months [390]. However, these preliminary results must be validated by larger randomized trials.…”
Section: Future Directionsmentioning
confidence: 99%
“…Although VEGFRs were postulated as mediators of sorafenib response in HCC, testing for VEGF-A serum levels was not found to be predictive of sorafenib treatment success ( 10 ). Moreover, bevacizumab, an antibody against VEGF-A, only shows minimal responses in HCC (17)(18)(19)(20). A possible explanation for this is that the mechanism of action of sorafenib is predominantly independent of VEGF-A inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Partial responses have been observed in patients after bevacizumab monotherapy and disease stabilisation in 30% of treated patients has been documented (Siegel et al, 2008). Combination treatment of bevacizumab with EGFR targeting agents was shown to be safe and revealed promising initial results with a median time to progression of 9 months (Thomas et al, 2007b) (see Table 1). Overall, bevacizumab has shown promising results as a single agent as well as in combination with other targeted therapies and cytotoxic therapy (Zhu et al, 2006) supporting the idea of a vascular targeting therapy for the treatment of HCC.…”
Section: Results From Phase I and Ii Studies Testing Other Approved Tmentioning
confidence: 99%